Aerobic and explosive power performance of elite Italian regional-level basketball players - Castagna, C.; Chaouachi, A.; Rampinini, E.; Chamari, K.; Impellizzeri, F. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to examine the aerobic fitness and lower-limbs explosive-power abilities of Italian regional-level amateur basketball players. Participants were basketball players playing successfully at a senior (S, n = 11) and junior (J, n = 11) regional level. Players maximal oxygen uptake (V?O2max) was assessed with them wearing a portable gas analyzer (K4b2, COSMED, Rome, Italy) during an exercise mode-specific multistage fitness test (yo-yo endurance test [Yo-Yo]). Knee extensors and plantar flexors explosive power was assessed with countermovement jump (CMJ) and stiff-leg jumps (SL), respectively. Jumps were performed using a switch mat connected to a computer (Muscle Lab, Bosco System, Rome, Italy). Jumps' fly (FT) and contact times (CT) were used for jump performances calculations. Stiff-Leg FT versus CT ratio (SL/CT) was considered as representative of lower-leg explosive power, whereas SL/CMJ·100 was considered as sign of the explosive-power balance between lower and upper leg muscles. Players' V?O2max was 60.88 ± 6.26 and 50.33 ± 3.98 mL·kg-1·min-1 for J and S, respectively (p < 0.05). A significant difference was found in SL/CT between S and J players. Yo-Yo performance was not significantly different between groups (2,055 ± 267 and 2,020 ± 174 m for S and J, respectively, p > 0.05). Lower-leg explosive power showed to be positively related to distance covered during Yo-Yo. Study results showed that 50 mL·kg-1·min-1 is a sufficient V?O2max value for competing at a regional level. Calf explosive power should be considered to improve sport-specific running performance in basketball using plyometrics and whole body lifts.